Prevalence and determinants of precancerous cervical lesions among women screened for cervical cancer in Africa: A systematic review and meta-analysis - Berihun Agegn Mengistie; Getie Mihret Aragaw; Tazeb Alemu Anteneh; Kindu Yinges Wondie; Alemneh Tadesse Kassie; Alemken Eyayu Abuhay; Wondimnew Mersha Biset; Gebrye Gizaw Mulatu; Nuhamin Tesfa Tsega (PLoS ONE, 2025)
Background Precancerous cervical lesions, or cervical intraepithelial neoplasia (CIN), represent a significant precursor to cervical cancer, posing a considerable threat to women’s health globally, particularly in developing countries. In Africa, the burden of premalignant cervical lesions is not well studied. Therefore, the main purpose of this systematic review and meta-analysis was to determine the overall prevalence of precancerous cervical lesions and identifying determinants among women who underwent cervical cancer screening in Africa. Methods This study followed the Preferred Reporting Item Review and Meta-analysis (PRISMA) guidelines. The protocol for this systematic review and meta-analysis was registered on the International Prospective Register of Systematic Reviews (PROSPERO) (ID: CRD42025645427). We carried out a systematic and comprehensive search on electronic databases such as PubMed and Hinari. In addition, Google Scholar and ScienceDirect were utilized to find relevant studies related to precancerous cervical lesions. Data from the included studies were extracted using an Excel spreadsheet and analyzed using STATA version 17. The methodological quality of the eligible studies was examined using the Joanna Briggs Institute (JBI) assessment tool. Publication bias was checked by using the funnel plot and Egger’s tests. A random-effects model using the Der Simonian Laird method was used to estimate the pooled prevalence of pre-cancerous cervical lesions in Africa. The I-squared and Cochrane Q statistics were used to assess the level of statistical heterogeneity among the included studies. Results A total of 112 eligible articles conducted in Africa, encompassing 212,984 study participants, were included in the quantitative meta-analysis. Thus, the pooled prevalence of pre-cancerous cervical lesions in Africa was 17.06% (95% confidence interval: 15.47%−18.68%). In this review, having no formal education (AOR = 4.07, 95% CI: 1.74, 9.53), being rural dweller(AOR = 2.38, 95% CI: 1.64, 3.46), history of STIs (AOR = 3.94, 95% CI: 2.97, 5.23), history of having multiple partners (AOR = 2.73, 95% CI: 2.28, 3.28), early initiation of coitus (AOR = 2.77, 95% CI: 2.11, 3.62), being HIV-seropositive women (AOR = 3.33, 95% CI: 2.32, 4.78), a CD4 count <200 cells/mm³ (AOR = 5.17, 95% CI: 1.70, 15.71), not being on ART (AOR = 2.58, 95% CI: 1.45, 4.58), smoking (AOR = 3.91, 95% CI: 1.43, 10.67) and prolonged use of oral contraceptive pills (AOR = 4.39, 95% CI: 2.77, 6.96) were significantly associated with precancerous cervical lesions. Conclusions In Africa, the overall prevalence of pre-cancerous cervical lesions is high (17%). The findings of this review highlight that health professionals, health administrators, and all other concerned bodies need to work in collaboration to expand comprehensive cervical cancer screening methods in healthcare facilities for early detection and treatment of cervical lesions. In addition, increasing community awareness and health education, expanding visual inspection of the cervix with acetic acid in rural areas, offering special attention to high-risk groups (HIV-positive women), encouraging adherence to antiretroviral therapy for HIV-positive women, overcoming risky sexual behaviors and practices, and advocating early detection and treatment of precancerous cervical lesions.